1992
DOI: 10.1128/jcm.30.7.1642-1645.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Staphylococcus aureus on the basis of coagulase gene polymorphisms

Abstract: Staphylocoagulase, a major phenotypic determinant of Staphylococcus aureus, exists in multiple allelic forms, in part because of the existence of gene variants within the 3'-end coding region. This region contains a series of repeating 81-bp DNA sequences which differ both in the number of tandem repeats and the location ofAluI restriction sites among different isolates. Utilizing this finding, we developed a novel typing method for S. aureus based on polymerase chain reaction amplification of the variable reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(175 citation statements)
references
References 18 publications
10
160
2
3
Order By: Relevance
“…According to the results of the present study the determination of the X region of the spa gene indicated that the strains of each pair possessed an identical size of the amplicon and an equal number of repeats. In addition, the gene polymorphism of the coa gene has been commonly used for molecular typing of S. aureus [11,30]. As Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of the present study the determination of the X region of the spa gene indicated that the strains of each pair possessed an identical size of the amplicon and an equal number of repeats. In addition, the gene polymorphism of the coa gene has been commonly used for molecular typing of S. aureus [11,30]. As Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2) after digestion with endonuclease SmaI; M: V DNA HindIII fragments, 0.1^200 kb, and V concatemers, 50^1000 kb. described by Goh et al [11] the discriminatory power relies on the heterogeneity of the region containing the 81bp DNA tandem repeats which di¡er in both in the number of tandem repeats and the location of AluI restriction sites among various isolates. The ampli¢cation of the coa gene of the isolates in the present study also showed an identity in each pair.…”
Section: Discussionmentioning
confidence: 99%
“…Provided that the PFGE method and interpretation are carefully standardized for a given microorganism, this method has robust reliability and intra-and inter-laboratory reproducibility (Goering, 2010). Similar DNA fragment-based methods have also been developed and used for clinical analyses including; restriction endonuclease fingerprinting analysis (REA) (Falk et al, 1985), plasmid typing (Farrar, 1983;Mayer, 1988;Nicolle et al, 1992), ribotyping (Thomson-Carter et al, 1989), PCR fingerprinting (Welsh and McClelland, 1990), restriction fragment length polymorphism (RFLP) (Goh et al, 1992;Metzgar et al, 1998), and amplified fragment length polymorphism (AFLP) (Vos et al, 1995;Meudt and Clarke, 2007). Multi-locus variable number tandem repeat analysis (MLVA) is another PCR-based method, which is used to determine the number and length of variable number tandem repeats (VNTRs) present in a genome due to slipped mispairing .…”
Section: Molecular Typingmentioning
confidence: 99%
“…With the coagulase gene RFLP method, individual strains can be easily compared by both the number of PCR-amplified gene products and the sizes of their restriction enzyme digest fragments. Because of the heterogeneity in the repeated unit-encoding locus, the coagulase gene, as has been shown in many publications (Goh et al, 1992;Schwarzkopf & Karch, 1994;Hooker et al, 1999;Raimundo et al, 1999), is a potential target for type classification on the basis of sequence analysis. Furthermore, nucleotide sequencing here provides an additional source of typing and a highly specific epidemiological marker with high discriminatory value.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous allelic forms of S. aureus coagulase exist, with each isolate producing one or more of these enemy variants (Henderson & Brodie, 1963;Reeves et al, 1981;Jeljaszewicz et al, 1983;Mandolo, 1990). Analysis of the DNA sequences of coagulase genes revealed that the variable sequences exist within the 3 0 coding regions of the allelic genes (Kaida et al, 1987(Kaida et al, , 1989Phonimdaeng et al, 1990) and different S. aureus isolates could be differentiated by virtue of these unique nucleotide sequences (Goh et al, 1992). This is a sensitive and specific method for the detection of colonization by S. aureus, but the complex nature of the biological samples as well as the low concentrations of analytes demand that cultures may still be needed to confirm positive results.…”
Section: Introductionmentioning
confidence: 99%